Katalisis CPO Menjadi Biodiesel Dengan Katalis ZnO Sintesis Presipitan NaOH - Mukhlisoh Arifah; Sri Helianty; Yusnimar Yusnimar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Biodiesel is an alternative renewable and biodegradable fuel with properties similar to petroleum diesel. It result of the conversion of vegetable oils derived from both non-foodand food ingredients which have economic value compared to fossil fuels. Heterogeneous catalysts such as ZnO in the manufacture of biodiesel can solve the problems of the use ofa homogeneous catalyst that can reduce the burden of separation, cheap, stable, and can be used repeatedly. This research aims to synthesize ZnO catalyst by precipitation method using NaOH. Then, the effect of variations in mole ratio of reactants and variations in the amount of catalyst on the yield of biodiesel produced will be studied. FFA content in thefeedstrock is 8,36%. Therefore, Biodiesel production process is carried out with a twostage reaction that is esterification and transesterification. The esterification reaction washeld at temperatures 65oC with H2SO4 catalyst as much as 1% w/w of oil. The transesterification reaction was held at temperatures 65oC; with H2SO4 catalyst as muchas 1% w/w of oil. The mole rato of oil : methanol are 1:6, 1:12, 1:18; ZnO catalyst amount are 0,3%, 0,4% and 0,5%; reacton time is 60 minnutes. The higest yield obtainedis 93,6% in process with 1:18 in oil : methanol mole ratio and 0,5% catalyst amount. The produced biodiesel has density 888 kg/m3, viscosity 5,63 mm2/s, flash point 175oC, acidvalue 0,53 mg-KOH/g-biodiesel and alkyl ester content 99,1%.Keywords : Biodiesel, CPO, esterification, transesterification, ZnO.